Entrepreneurship and Strategic Management: A Critical Analysis on these Paradigms' Relationship - Shah, Gyanendra Bikram (Pravaha, 2020)
The purpose of this study is to provide a better understanding of the arguments concerning the various views provided by different academics in the fields of entrepreneurship and strategic management and then to find a position in which practice is generally agreed on by the divisions. The researcher examined the fundamental theories of the two paradigms of entrepreneurship and strategic management and also examined existing literature submitted by scholars in the fields who tried to look at the intersection of the two paradigms. This post, however, aims to highlight the need to see the two disciplines as being similar from various parental perspectives. Literature on each of the paradigms was checked to provide a better understanding of them. The researcher was able to consider such intersecting variables, such as culture, which was seldom stressed as a factor influencing the opportunity-seeking conduct of an entrepreneur and competitive advantage-seeking activities to create wealth and ensure the economic development and survival of an organization.